The paradox of climate policy diffusion - Ivan Savin; Philipp Mundt; Margherita Bellanca (Bamberg University, Bamberg Economic Research Group (BERG), 2024)
Prior research produced contradicting evidence regarding the role of international influence in the diffusion of climate policies. To unravel this puzzle, we examine various policy instruments adopted by G20 countries, demonstrating that peer pressure stimulates convergence in the number of new policies adopted but divergence in their stringency. This suggests that policymakers emulate the appearance of their peers but not the rigor of regulation, creating opportunities for carbon leakage.
Keywords: C21; F18; F42; F64; Q56; 330; climate change; market instruments; policy adoption; variance decomposition; spatial model